Histological study of Culex pipiens pipiens larvae and adults infected with Beauveria bassiana (Baghdad Science Journal, 2012)
This study aimed to show the histological changes that 0ccured in Culex pipiens pipiens larvae and adults infected with Beauveria bassiana . The 4th instar larvae and adult mosquitoes were infected with B.bassiana in 10-4 spore/ml dilution, after 96 hours histological section was studied showing that the fungi infected all the body parts specially Cuticle , Epiderms, fat bodies and midgut. After 120 hours of exposure to the fungi the insect have a white appearance and covered with a thick coat of hyphea. Thus study shows biological control of B .bassiana on mosquitoes.